Effective use of hybrid turbine ventilator to improve thermal performance in Malaysian tropical houses - Al-Obaidi, K.M.; Ismail, M.A.; Abdul Rahman, A.M. (SAGE Publications, 2016)
An efficient design approach that involves extracting heat build-up in tropical buildings is a means to reduce total dependency on air-conditioning systems. The hybrid turbine ventilator can be regarded as a development technique to address this issue. However, identifying its efficient application in buildings remains questionable. This study aims to develop the research on the hybrid turbine ventilator for the establishment of energy-efficient designs in houses by evaluating its effective use in specific space volume based on several empirical comparisons. The performance of passive and hybrid turbine ventilators in attic space, room, and (attic space + room) with opened and closed windows was compared. The study was conducted in an actual building model, and data were collected onsite with a data acquisition system. The objective was achieved by investigation, and the findings can be used to identify the levels of heat build-up in each strategy. Examination of thermal performance confirmed the appropriate use of the hybrid turbine ventilator in Malaysian landed houses. Practical application:This research contributes directly to energy efficient design in tropical buildings. The outcomes inform a better decision on the effective use of hybrid turbine ventilator in low-rise buildings. The study provides ample evidence on the great potential of using hybrid turbine ventilator by developing its investigation in tropical architecture. The study will assist engineers and architects to evaluate hybrid turbine ventilator performance effectively.